Effect Performance Of Posyandu Toddlers Cadre Against Satisfaction Level Mother Of Toddlers At Posyandu Melati 9 Health Center Liliba Kota Kupang - Taek, Joice D; Tnomel, Kristoforus; Oeleu, Sefrianus (Universitas STRADA Indonesia, 2018)
Background: One of the problems that is often faced today is the disability of under-five mothers in obtaining health services for children under five years old because of the lack of performance of Posyandu health workers. Purpose : The purpose of this research is to know the Effect Performance Of Posyandu Toddler Cadres Against Satisfaction Level Of Toddler Mother At Posyandu Melati 9 Health Center Liliba Kota Kupang Methods : The design of this study used an observational quantitative approach with cross sectional approach. Respondents were taken with Simple Random Sampling technique. Population studied All Mothers Under Five at Posyandu Melati 9 Puskesmas Liliba Kota Kupang with sample 39 mother. Independent Variables studied is the Performance of Posyandu Toddler and Dependent Variable is the Level of Satisfaction of Under-five Mother. The results were analyzed by using Ordinal Regression statistic test. Result : The results showed that Kader Performance is known that almost half of the respondents in the Good category is as many as 14 (36%) of respondents. Satisfaction rate of Underfive Mothers is known that most respondents in the category Very Satisfied is as much as 20 (51%) respondents. The result of data analysis shows that the significance level of 0,000 <? = 0.05 so that H0 is rejected and H1 is accepted thus There is Effect Performance Of Posyandu Toddler Cadres Against Satisfaction Level Of Toddler Mother At Posyandu Melati 9 Health Center Liliba Kota Kupang. Conclusion : Based on the result of the research, it is known that the satisfaction of mother of balita to posyandu service where cadre always do monitoring and evaluation to posyandu. Besides, it is also supported by cadre training and comparative study of posyandu cadres to other posyandu as a learning media so that they can follow the improvement effort that has been done